Quality improvement strategy of implementation community-based total sanitation program in Samarinda, Indonesia - Al Syahrin, M Najeri; Badrian, Badrian; Syamsir, Syamsir; Rahmi, Nispan; Faridah, Faridah; Rusdiyah, Rusdiyah; Nadiyah, Nadiyah (Technium Social Sciences Journal, 2023)
Community-Based Total Sanitation (STBM) is a program that aims to change the behavior of community sanitation hygiene through empowerment programs. The quality of STBM program implementation varies by city. The strategy implemented by the health office of the city influences the quality of the STBM program. Based on these problems, a comprehensive study is needed to find out strategies that can improve the quality of STBM program implementation. This study aims to determine the strategies used by the health department in improving the quality of STBM program implementation in Samarinda City. The stages of data collection in this research were carried out in two ways, namely document-based literature study and interviews. Documents collected are STBM activity reports and health profiles from 2012 – 2018. The implementation of the Community Based Total Sanitation (STBM) program in Samarinda City has involved cross-sectoral. Since 2014, the government of Samarinda City has supported the STBM program by increasing the annual budget for implementing the STBM program. Based on interviews with Samarinda City Health Office informants, the obstacle faced in improving the quality of STBM program implementation was the lack of health workers trained in STBM fields. Samarinda City Government has also provided support for maximizing the STBM program through the Samarinda Mayor Circular. There are four strategies used by the Health Office of Samarinda City in improving the quality of STBM program implementation. The first strategy is the involvement of sub-district heads and natural leaders in organizing and implementing STBM programs. Second, a large increase in the STBM budget every year. Third, improving the quality of environmental health workers in supporting the maximization of the STBM program. Fourth, the making of regulations from the local government related to the implementation of STBM in each district and village.